Effects of the Nd : YAG laser, air-abrasion, and acid-etchant on filling materials - TÜRKMEN, CAFER; GÜNDAY, MAHİR (BLACKWELL PUBLISHING, 2006)
The purpose of this study was to determine any inadvertent effects of the neodymium: yttrium-aluminium-garnet (Nd:YAG) laser, air-abrasion, and ortho-phosphoric acid on some conventionally used dental filling materials [amalgam, composite resin, compomer, glass-ionomer cement (GIC), and ceromer], when they were used for purposes of margin etching and assessed according to standard enamel etching parameters using a total of five fillings. The surfaces of the filling materials were polished. One sample from each material group was exposed to laser (at 0.75 J, 15 pps) and air abrasion (with Al-oxide powder, 60 psi) for 2 s and to the 37% ortho-phosphoric acid for 60 s. The exposed materials were examined under Scanning Electron Microscopy (SEM). After laser treatment most specimens showed recrystallized areas, the GIC surface being the most affected. There were some pores and cavities on the amalgam surface following laser treatment. The abraded surfaces showed mechanical abrasions. The acid etchant showed the least effect. During the application of laser or air-abrasion, the adjacent tooth or filling surface must be protected or the dentist must be careful.
Keywords: Nd : YAG laser; air-abrasion; acid-etching; filling materials; BOND STRENGTH; DENTIN; ENAMEL; IRRADIATION; SURFACE; CARIES